Kemerosotan Norma Keamanan Manusia dalam Kebijakan Imigrasi Australia Setelah Tahun 1992 - Gema Ramadhan Bastari (Universitas Airlangga, 2018)
This paper will discuss about the degeneration of human security as a norm that dictates Australia’s immigration policy. As one of the originator of 1951 United Nations Convention Relating to the Status of Refugees, Australia should comply to the idea that refugee must be protected at all costs, even if they went through irregular channel of migration. However, the tightening of Australia’s immigration since 1992 puts this compliance under serious question. The fact that every irregular immigrants entering Australia has to be either detained in an offshore detention center for indefinite amount of time or getting turned back by naval ship means that Australia can no longer tolerate irregular immigration. While this act can probably be justified if those immigrants are part of people smuggling scheme, the same cannot be said if those immigrants were a genuine refugee. In that regard, this paper argues that the norm of human security in Australia has been degenerating and got replaced by the norm of state security. This argument will be proven by using the theory of norm diffusion. However, since the theory cannot explain why certain international norms disappear, this paper will complement it by using the theory of norm degeneration. This paper concludes that globalization and the rise of international terrorism is the biggest factor for the degeneration of human security norm in Australia.